The Role of Guidance and Counseling Teachers in Anticipating Students' Aggressive Behavior Tendencies at SMP Negeri 1 Galang - Cordelia, Meisyara; Hartika, Rahma Sinta Dewi; Lesmana, Gusman (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This research method qualitative descriptive research. Subject and object in this research are the principal, headmaster, teacher guidance and counseling and student. Instrumen used in this study were interviews, observation and documentation. The results showed that (1) the cause learners to behave aggressive is largely because the character of the students was loud and tend to assumes that the behavior, they are doing is a fairness and because the lack of supervision, attention and affection from parents so that children tend to feel able to do any desired and (2) the role of the teacher guidance and counseling in reducing aggressive behavior students is good enough to provide individual counseling